ERQTM: Energy-Efficient Routing and QoS-Supported Traffic Management Scheme for SDWBANs - Samarji, Nivine; Salamah, Muhammed (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
Maintaining the network QoS is one of the critical challenges emerging in heterogeneous WBANs. High throughput, minimum delay, and maximum lifetime are the critical network performance metrics pre-requisites for achieving the network QoS. The use of Software-Defined Networking (SDN) concept has been recently adopted in dynamic and complex structured WBANs due to the existence of wide network management flexibility. Leveraging the benefits of SDN in cognitive radio (CR) based architectures, we have presented ERQTM: Energy-efficient Routing and QoS-supported Traffic Management scheme for SDWBANs. The main contributions of the proposed scheme are enhancing the network lifetime and achieving the network stability and reliability. Thus, the problem is addressed through a joint scheme, developing an energy-efficient routing scheme (ER) and traffic management scheme. The proposed ERQTM framework is fundamentally based on network clustering which proves to have positive impact on overall network delay. As clustering is an optimizing and an NP-Hard problem, this paper adopts genetic algorithm to optimally find the required cluster heads (CHs) in the ER scheme taking into consideration the nodes-related matters: residual energy, energy consumption rate during consecutive intervals, distance to the SDN controller, signal to noise ratio, and the path loss model. Besides clustering, prioritizing the emergency data (ED) in the traffic management scheme is presented that efficiently handles the packets by ensuring free-delay for ED transmission. This is done by assigning high priority for routing, high data rate, and needed-related power. Performance evaluation results showed that the proposed ERQTM scheme has outperformed different priority-based state-of-the-art schemes.
Keywords: Software-defined networking; wireless body area network; QoS metrics; energy-efficient routing algorithm, and traffic management